Respuesta :
Answer:
[tex]x= \frac{-7+\sqrt{697}}{8}[/tex]
[tex]x= -\frac{7+\sqrt{697}}{8}[/tex]
Step-by-step explanation:
4(x+3)-4 = 81/2x +1
Add 4 to both sides
4(x+3) = 81/2x +5
Multiply both sides by 2x (This removes the division from the second half)
8x(x+3) = 81 +10x
Simplify
[tex]8x^{2}[/tex]+24x = 81 +10x
Subtract 10x from both sides
[tex]8x^{2}[/tex] +14x = 81
Subract 81 from both sides
[tex]8x^{2}[/tex] +14x -81 = 0
Solve using the quadratic formula
[tex]x= \frac{-b (+-) \sqrt{b^{2} -4ac}}{2a}[/tex]
a= 8, b= 14, c= -81
[tex]x = \frac{-14 (+-) \sqrt{14^{2} -4 *8(-81)} }{2*8}[/tex]
Simplify
[tex]\sqrt{14^{2} -4 *8(-81)} = 2\sqrt{967}[/tex]
[tex]\frac{-14 (+-) 2\sqrt{967}}{2*8}[/tex]
Simplified Solution
[tex]x= \frac{-7+\sqrt{697}}{8}[/tex]
And
[tex]x=- \frac{7+\sqrt{697}}{8}[/tex]
I know this is confusing but I hope it helps. Keep in mind that (+-) means plus or minus. You might also look up what the quadratic formula is if you are not already familiar with it.